Observations on Groundwater Contamination with Nitrogen Compounds: A Case Study from Medias town, Sibiu County - Maria Alexandra HOAGHIA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2017)
Worldwide, the groundwater (water well and public spring) is used as drinking water source. The water quality is important due to the possible negative effects on the consumers’ health, especially for infants. Nitrogen compounds (NO2-, NO3-, NH4+) are present as natural components of the nitrogen cycle and their presence in the groundwater is ubiquitous. But, due to the anthropogenic activities high concentrations of nitrogen compounds are release into the groundwater, thereby the chemical compounds concentrations exceed the maximum allowable concentrations (MACs). The purpose of the present study was to assess the content of nitrogen compounds in groundwater, namely private water wells and public springs used as drinking water sources by the Medias town population. The study results show alarming NO2- and NO3- concentrations; the NO3- concentrations exceed 5 times the MAC and NO2- concentrations exceed3 times the MAC.